Vertical and Horizontal Agency Problems in Private Firms: Ownership Structure and Operating Performance - Gogineni, Sridhar; Linn, Scott C.; Yadav, Pradeep K. (Journal of Financial and Quantitative Analysis, 2022)
Abstract We investigate how ownership structure influences operating performance and implied agency costs. Our sample includes over 42,000 U.K. private and public firms. We document several new results of considerable economic significance relating to i) horizontal agency costs arising from unequal ownership within private firms, ii) amplification of agency costs from joint presence within the same firm of horizontal agency problems and vertical agency problems arising from separation of ownership and control, iii) mitigation in agency costs wrought by a second large shareholder, iv) impact of complex ownership structures, and v) agency cost differences between public firms and comparable private firms.